Pengembangan Sistem Informasi Deteksi Stunting Berbasis Android Menggunakan Metode Z-Score - Nidia Enjelita Saragih; Elida Tuti Siregar (Universitas Methodist Indonesia, 2026)
Stunting is one of the major chronic nutritional problems in Indonesia that affects children's growth and development. The manual process of detecting stunting often leads to delays in handling and potential inaccuracies in determining nutritional status. Therefore, a system is needed to support faster and more accurate detection. This study aims to develop an Android-based stunting detection information system using the Z-score method. The research method used is Research and Development (R&D) with the Waterfall model, which includes requirement analysis, system design, implementation, and testing stages. The data used in the calculation refers to the growth standards established by the World Health Organization (WHO). The results show that the developed system is capable of automatically calculating Z-score values based on user input, including age, height, and weight of the child. The system can also accurately determine the nutritional status according to WHO classification standards. Based on Black Box Testing, all system functions run properly as expected. Thus, the developed information system can assist the community and health workers in conducting early detection of stunting more effectively and efficiently.